2018
DOI: 10.4103/jehp.jehp_107_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the results of faculty evaluation in Isfahan University of Medical Sciences

Abstract: OBJECTIVE:This study aimed to explore factors influencing the results of faculty member evaluation from the viewpoints of faculty members affiliated with Isfahan University of Medical Sciences, Isfahan, Iran.MATERIALS AND METHODS:This qualitative study was done using a conventional content analysis method. Participants were faculty members of Isfahan University of Medical Sciences who, considering maximum variation in sampling, were chosen with a purposive sampling method. Semi-structured interviews were held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Insufficient knowledge of physicians in the estimation of prognosis and lack of sufficient knowledge about the legal aspects of the work lead to ineffective communication and care for patients 62. Therefore, the observance of ethical aspects aiming at serving the community and responding to the needs of society require the acquisition of extensive academic knowledge 63…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient knowledge of physicians in the estimation of prognosis and lack of sufficient knowledge about the legal aspects of the work lead to ineffective communication and care for patients 62. Therefore, the observance of ethical aspects aiming at serving the community and responding to the needs of society require the acquisition of extensive academic knowledge 63…”
Section: Discussionmentioning
confidence: 99%
“…They believed that this difference was caused by the unique context and environment in each school. 14 Maroofi 15 also stated that the quality of the educational environment and the students could affect the quality of teaching, and consequently evaluation results. In most departments and over years, the evaluation scores given by the administrators were higher than those of the students due to consideration of interpersonal communications.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn will eventually lead to being able to effectively deal with challenges within the organization and be able to appropriately cope with difficulties and changes within the organization (Nikolaou and Tsaousis, 2002;Dulewicz et al, 2003). A similar study found that the relationship between components of self-awareness and self-management and attitudes were also of significance (Yamani et al, 2014). Whereas Jung and Yoon (2016) found that self-awareness has no significant effect on job satisfaction.…”
Section: Attitudes Job Satisfactionmentioning
confidence: 95%